Pengaruh Kegiatan Melukis dengan Menggunakan Bahan Alam terhadap Kreativitas Anak di Taman Kanak-Kanak Asdani - Arida Supiyati; Azizah Amal; Rusmayadi (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2023)
The purpose of this study was to determine the impact of painting activities using natural materials on children's creativity at Asdani Kindergarten. This study was conducted using a quantitative approach with a quasi-experimental research design. with a population of 35 children using simple random sampling with a sample of 8 children each in the experimental and control groups. Descriptive and non-parametric statistical analysis was used to collect data. The results of the data analysis obtained an average increase in the experimental group of 6.25 and in the control group of 1.37. The test results showed a sig. (2-tailed) 0.011 <0.05, then H0 is rejected and H1 is accepted. So it can be concluded that painting using natural materials has a significant effect on children's creativity at Asdani Kindergarten.